2022
DOI: 10.1002/ejhf.2526
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival of left ventricular assist device carriers in Europe according to implantation eras: results from the PCHF‐VAD registry

Abstract: Temporal changes in patient selection and major technological developments have occurred in the field of left ventricular assist devices (LVADs), yet analyses depicting this trend are lacking for Europe. We describe the advances of European LVAD programmes from the PCHF-VAD registry across device implantation eras.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Another challenge in Europe and the UK has emerged with inconsistent reimbursement for DT LVAD implantation due to concerns over cost‐effectiveness 4 . In this context, the timely report by Jakus and colleagues in the Journal provides a fertile opportunity to compare and contrast epidemiological trends in LVAD effectiveness across the US and Europe 13 . As they report, the archetypal LVAD recipient in Europe tends to be an advanced HF patient, not yet requiring inotropic therapy, who is maintained as a bridge to HT but is likely to accrue several years on LVAD support, in essence similar to DT indication.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Another challenge in Europe and the UK has emerged with inconsistent reimbursement for DT LVAD implantation due to concerns over cost‐effectiveness 4 . In this context, the timely report by Jakus and colleagues in the Journal provides a fertile opportunity to compare and contrast epidemiological trends in LVAD effectiveness across the US and Europe 13 . As they report, the archetypal LVAD recipient in Europe tends to be an advanced HF patient, not yet requiring inotropic therapy, who is maintained as a bridge to HT but is likely to accrue several years on LVAD support, in essence similar to DT indication.…”
Section: Figurementioning
confidence: 99%
“…14 This programme has now trained several hundreds of clinicians across Europe and beyond, and also allowed for development of research networks and clinical collaborations among its alumni. The report by Jakus et al 13 in the Journal represents an important output from the PCHF-VAD launched LVAD registry, a multinational effort across 13 European tertiary HF centres and 10 countries. As 15 exemplifies, such a network can define gaps and help to harmonize practices across centres within a persuasive framework.…”
Section: This Article Refers To 'Improved Survival Of Left Ventricula...mentioning
confidence: 99%
“…In both allogeneic and orthotopic heart transplantation, the donor heart faces denervation and is vulnerable to a variety of cardiovascular events in the absence of central innervation, such as arrhythmias, abnormal chest pain, sudden atrial fibrillation, sudden cardiac death, and stroke ( Joglar et al, 2021 ; Firoz et al, 2022 ). With the popularity of the heart transplantation approach and extensive research, it has been reported that the sympathetic nerves of the heart gradually regenerate over time, restoring sympathetic innervation to the heart and participating in the rhythm regulation of the heart and the perfusion of the heart muscle ( Jakus et al, 2022 ). The state of cardiac transplant sympathetic reinnervation varies from one heart transplant patient to another, with some heterogeneity in various regions of the heart ( Wilson et al, 1991 ).…”
Section: Reinnervation Of a Transplanted Heartmentioning
confidence: 99%
“…However, they also had lower 1‐year mortality rates, lower chances of heart transplantation and less LVAD‐related infections. Better survival in the second era may be explained by advances in technology, along with a greater centres' expertise 19 …”
Section: Devicesmentioning
confidence: 99%
“…Better survival in the second era may be explained by advances in technology, along with a greater centres' expertise. 19…”
Section: Devicesmentioning
confidence: 99%